Photochemistry in the arctic free troposphere: Ozone budget and its dependence on nitrogen oxides and the production rate of free radicals - Stroud, Craig; Madronich, Sasha; Atlas, Elliot; Cantrell, Christopher; Fried, Alan; Wert, Brian; Ridley, Brian; Eisele, Fred; Mauldin, Lee; Shetter, Richard; Lefer, Barry; Flocke, Frank; et al. (DigitalCommons@URI, 2004)
Local ozone production and loss rates for the arctic free troposphere (58-85° N, 1-6 km, February-May) during the Tropospheric Ozone Production about the Spring Equinox (TOPSE) campaign were calculated using a constrained photochemical box model. Estimates were made to assess the importance of local photochemical ozone production relative to transport in accounting for the springtime maximum in arctic free tropospheric ozone. Ozone production and loss rates from our diel steady-state box model constrained by median observations were first compared to two point box models, one run to instantaneous steady-state and the other run to diel steady-state. A consistent picture of local ozone photochemistry was derived by all three box models suggesting that differences between the approaches were not critical. Our model-derived ozone production rates increased by a factor of 28 in the 1-3 km layer and a factor of 7 in the 3-6 km layer between February and May. The arctic ozone budget required net import of ozone into the arctic free troposphere throughout the campaign; however, the transport term exceeded the photochemical production only in the lower free troposphere (1-3 km) between February and March. Gross ozone production rates were calculated to increase linearly with NOx mixing ratios up to ∼300 pptv in February and for NOx mixing ratios up to ∼500 pptv in May. These NOx limits are an order of magnitude higher than median NOx levels observed, illustrating the strong dependence of gross ozone production rates on NOx mixing ratios for the majority of the observations. The threshold NOx mixing ratio needed for net positive ozone production was also calculated to increase from NOx ∼ 10 pptv in February to ∼25 pptv in May, suggesting that the NOx levels needed to sustain net ozone production are lower in winter than spring. This lower NOx threshold explains how wintertime photochemical ozone production can impact the build-up of ozone over winter and early spring. There is also an altitude dependence as the threshold ...